Response of Baby Corn Plants toward Concentration of Granule Zeolite and Duration of Zeolite Soaking in Cow Urine - Kardaya, Dede; Rahayu, Arifah; Rudiansyah, Didi (JURNAL AGRONIDA, 2019)
The study was done to assess the effect of zeolite concentration and time of zeolite soaking in cow urine on the growth and production of baby corn. A factorial completely randomized design with two factors was used. The first factor was zeolite concentration (0%, 5% and 10%). The second factor was soaking time in cow urine (1,2,3 and 4 weeks). Results showed that corn plants treated with 0% zeolite (fermented urine) have higher stem circumference, leaves color intensity and higher cob weight. Plants that were given a concentration of 5% zeolite produced male flowers late. The duration of zeolite immersion in cow urine did not significantly affect all observed variables. Keywords: stem circumference, male flowers, baby corn, zeolite